2000
DOI: 10.1182/blood.v96.2.763
|View full text |Cite
|
Sign up to set email alerts
|

Microchimerism in bone marrow–derived CD34+ cells of patients after liver transplantation

Abstract: Lymphoid and dendritic cells of donor origin can be detected in the recipient several years after a solid organ transplantation. This phenomenon is termed microchimerism and could play a role in the induction of tolerance. The fate of other hematopoietic cells transferred by liver transplantation, in particular of stem and progenitor cells, is unknown. For this reason, we studied peripheral blood and bone marrow samples of 12 patients who had received a liver transplant from an HLA-DR mismatched donor. Eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Despite the success of PBSC transplantation, the exact mechanisms involved in PBSC mobilization and homing are not yet clear. In adults, small amounts of PBSC are present in the peripheral blood (PB) during steady state haematopoiesis, as has been known for 40 years (Goodman & Hodgson, 1962; Dorie et al , 1979; Fruehauf et al , 1995), suggesting a continuous migration and exchange of haematopoietic stem cells between the bone marrow (BM) and other organs, such as the liver and spleen (Starzl et al , 1996; Nierhoff et al, 2000). This model is strongly supported by experiments in which parabiotic mice were surgically conjoined and shared a common circulation (Wright et al, 2001).…”
Section: The Success Story Of Pbsc Transplantationmentioning
confidence: 98%
“…Despite the success of PBSC transplantation, the exact mechanisms involved in PBSC mobilization and homing are not yet clear. In adults, small amounts of PBSC are present in the peripheral blood (PB) during steady state haematopoiesis, as has been known for 40 years (Goodman & Hodgson, 1962; Dorie et al , 1979; Fruehauf et al , 1995), suggesting a continuous migration and exchange of haematopoietic stem cells between the bone marrow (BM) and other organs, such as the liver and spleen (Starzl et al , 1996; Nierhoff et al, 2000). This model is strongly supported by experiments in which parabiotic mice were surgically conjoined and shared a common circulation (Wright et al, 2001).…”
Section: The Success Story Of Pbsc Transplantationmentioning
confidence: 98%
“…We have shown that after liver transplantation, donor-specific CD34 ϩ cells could be detected in the recipient's BM [55]. In a recent report, Körbling et al [56] provided indications that stem cells derived from peripheral blood could differentiate into mature hepatocytes and epithelial cells of the skin and gastrointestinal tract.…”
Section: Reinventing Hscmentioning
confidence: 68%
“…Long-term repopulating HSC cannot be expanded in vitro without losing developmental potential [1]. Verfaillie and her group [51,52,55] have however recently demonstrated that MAPC could proliferate without obvious senescence under clinically applicable conditions. However, these data need to be confirmed and validated by other groups.…”
Section: Relative Merits Of Adult and Es Cellsmentioning
confidence: 99%
“…This was also the conclusion of Miller et al, 57 who suggested that donor cells resident in the recipient marrow might be of primary importance in mediating the immunomodu‐lation necessary for tolerance. It has been shown recently that CD34+ cells of donor origin can be demonstrated in recipient marrow years after liver transplantation 58 …”
Section: Tolerance Augmentation With Donor Cell Infusionsmentioning
confidence: 99%